Rethinking Obesity Counseling: Having the French Fry Discussion - Jonathan Bonnet; Aaron George; Pippa Evans; Mina Silberberg; Diana Dolinsky (Journal of Obesity)
Childhood obesity is a complex problem that warrants early intervention. General recommendations for obesity prevention and nutrition counseling exist. However, these are notably imprecise with regard to early and targeted interventions to prevent and treat obesity in pediatric populations. This study examines family medicine primary care providers’ (PCPs) perceived barriers for preventing and treating pediatric obesity and their related practice behavior during well-child visits. Methods. A written survey addressing perceived barriers and current practices addressing obesity at well-child visits were administered to PCPs at eleven family medicine clinics in the Duke University Health System. Results. The most common perceived barriers identified by PCPs to prevention or treatment of obesity in children were families not getting enough exercise (93%) and families too often having fast food meals (86%). Most PCPs do not discuss fast foods at or prior to the twelve-month well-child visit. The two-year visit is the first well-child visit at which a majority of PCPs (68%) discuss fast food. Conclusion. No clear consensus exists as to when PCPs should discuss fast food in early well-child checks. Previous research has shown a profound shift in children’s dietary habits toward fast foods, such as French fries, that occurs between the one- and two-year well-child checks. Consideration should be given to having a “French Fry Discussion” at every twelve-month well-child care visit.